2012
DOI: 10.1128/jb.00779-12
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Poly(3-Hydroxybutyrate) (PHB) Granule-Associated Proteins during PHB Granule Formation and Identification of Two New Phasins, PhaP6 and PhaP7, in Ralstonia eutropha H16

Abstract: Poly(3-hydroxybutyrate) (PHB) granules are covered by a surface layer consisting of mainly phasins and other PHB granuleassociated proteins (PGAPs). Phasins are small amphiphilic proteins that determine the number and size of accumulated PHB granules. Five phasin proteins (PhaP1 to PhaP5) are known for Ralstonia eutropha. In this study, we identified three additional potential phasin genes (H16_B1988, H16_B2296, and H16_B2326) by inspection of the R. eutropha genome for sequences with "phasin 2 motifs." To det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
64
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 56 publications
8
64
1
Order By: Relevance
“…This finding is in agreement with previous contributions of others (41). In our earlier studies on PHB granule formation, we showed by fluorescence microscopy that newly synthesized PHB granules occurred very rapidly within 5 min after application of PHB permissive conditions in starved (PHB-free) cells of R. eutropha (i.e., after transfer of starved cells to fresh NB-gluconate medium) (24). If a PHB granule of ϳ250 nm in diameter is formed in the cells within only 5 min, it is unlikely that PHB synthase has a significant lag phase of 2 to 4 min in vivo.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…This finding is in agreement with previous contributions of others (41). In our earlier studies on PHB granule formation, we showed by fluorescence microscopy that newly synthesized PHB granules occurred very rapidly within 5 min after application of PHB permissive conditions in starved (PHB-free) cells of R. eutropha (i.e., after transfer of starved cells to fresh NB-gluconate medium) (24). If a PHB granule of ϳ250 nm in diameter is formed in the cells within only 5 min, it is unlikely that PHB synthase has a significant lag phase of 2 to 4 min in vivo.…”
Section: Resultssupporting
confidence: 81%
“…The micelle model was the favorite model for many PHA researchers in the past. However, this model cannot explain the nonrandom localization of "early" PHB granules, i.e., the frequent observation of PHB granules near the cell center in nongrowing cells (46)(47)(48) or the finding of peripherylocated PHB granules in growing cells (24,45,49). Nucleoid occlusion of PHB granules (50) in growing cells might be one explanation for the frequent observation of periphery-localized PHB granules, and this assumption would allow to keep the micelle model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only the proteins that colocalize with PHB granules are true in vivo PGAPs. This method has been used to confirm the subcellular localization of PHB synthases, phasins, and PHB depolymerases (32)(33)(34)(35)(36)(37)(38)(39). Because of the high number (Ͼ400) of proteins identified in the PHB granule fraction by proteome analysis (29), the in vivo confirmation of their subcellular localizations would require the construction of hundreds of fusions with green fluorescent protein.…”
mentioning
confidence: 99%
“…Later on, six other phasins (PhaP2 to PhaP7) were detected, and all of them were detected at the surface of PHB granules during in vivo or in vitro binding studies. However, the amount of PhaP1 at the surface of PHB granules is by far the largest in comparison to the amounts of other phasins (15)(16)(17). The phasins coat the PHB granules, but a catalytic function remains unknown so far.…”
mentioning
confidence: 99%